Yes, or No? Is there an effect of leukemia drugs on bacteria isolated from different sites of ALL and AML patients? - Helo, Zynab S.; N. Naji, Eman; A. Shubber, Mazin (Journal of Neonatal Surgery, 2025)
Objective: The current research aims to evaluate the prevalence of causative bacterial species in acute myeloid and lymphoblastic leukemia patients, as well as the effect of certain chemotherapeutic agents on the growth of common bacterial pathogens isolated from various sites in these patients. Additionally, it investigates the relationship between elevated minimum inhibitory concentrations (MICs) of chemotherapeutic drugs and antimicrobial resistance. Methods: This study included 200 patients who attended HTC in Medical City during a period between October 2023 to January 2024, ranging in age from 14 to 81 years. Blood, urine, sputum and swab samples were collected from various sites, including skin and throat swabs. The isolates were identified through phenotypic examination and biochemical tests, and confirmed by VITEK-2 assay. Antibiotic susceptibility pattern and the ability to form biofilms were studied for all bacterial isolates, followed by MIC testing for chemotherapeutic drugs including Cytarabine and Decitabine. Results: Statistical analysis indicated significant differences (p ≤ 0.05) in age between ALL and AML patients with and without fever notable discrepancies were observed in the age groups of both ALL and AML patients. While highly significant differences were indicated a distribution of 195 isolates into gram-positive and gram-negative categories, no significant correlation was observed between the type of bacteria and their sources .Synergistic effects were detected among certain antibiotics against bacteria isolated from various sources. Comparing groups revealed significantly higher differences in PCT concentration associated with both ALL and AML with fever when considering bacterial group .Also significant distinction was recorded among the analyzed groups of gram-positive and gram-negative bacterial isolates in ALL and AML patients concerning the mean concentration of CRP. No inhibitory effects were noticed across all minimum inhibitory concentration (MIC) values for both chemotherapy agents Cytarabine and Decitabine towards various multidrug-resistant bacterial isolates obtained from different sources.